Co-transplantation of Mesenchymal Stromal Cells and Induced Pluripotent Stem Cell-Derived Cardiomyocytes Improves Cardiac Function After Myocardial Damage - Neef, Klaus; Drey, Florian; Lepperhof, Vera; Wahlers, Thorsten; Hescheler, Jürgen; Choi, Yeong-Hoon; Šarić, Tomo (Frontiers in Cardiovascular Medicine, 2022)
Induced pluripotent stem cell-derived cardiomyocytes (iPS-CMs) represent an attractive resource for cardiac regeneration. However, survival and functional integration of transplanted iPS-CM is poor and remains a major challenge for the development of effective therapies. We hypothesized that paracrine effects of co-transplanted mesenchymal stromal cells (MSCs) augment the retention and therapeutic efficacy of iPS-CM in a mouse model of myocardial infarction (MI). To test this, either iPS-CM, MSC, or both cell types were transplanted into the cryoinfarction border zone of syngeneic mice immediately after injury. Bioluminescence imaging (BLI) of iPS-CM did not confirm enhanced retention by co-application of MSC during the 28-day follow-up period. However, histological analyses of hearts 28 days after cell transplantation showed that MSC increased the fraction of animals with detectable iPS-CM by 2-fold. Cardiac MRI analyses showed that from day 14 after transplantation on, the animals that have received cells had a significantly higher left ventricular ejection fraction (LVEF) compared to the placebo group. There was no statistically significant difference in LVEF between animals transplanted only with iPS-CM or only with MSC. However, combined iPS-CM and MSC transplantation resulted in higher LVEF compared to transplantation of single-cell populations during the whole observation period. Histological analyses revealed that MSC increased the capillarization in the myocardium when transplanted alone or with iPS-CM and decreased the infarct scar area only when transplanted in combination with iPS-CM. These results indicate that co-transplantation of iPS-CM and MSC improves cardiac regeneration after cardiac damage, demonstrating the potential of combining multiple cell types for increasing the efficacy of future cardiac cell therapies.